An overview of georeferenced chromosomes numbers of Moroccan Asteraceae - Gounssa, Abdelkarim; OUAREG, Zakaria; EL ABOUDI, Ahmed; TAHIRI, Hikmat; GUENNOUN, Naima; SEMMLING, Bonnie; EL GASMI, Omar (Mediterranean Botany, 2025)
In Moroccan vascular flora, the Asteraceae family ranks first in terms of specific richness. However, there is no up-to-date account of the geographic distribution of its species with established chromosome numbers. In this contribution, we inspected the chromosome number of Moroccan Asteraceae published in former studies; a synonym glossary is given, the names were verified and updated to the recent and accepted ones, by using Moroccan flora Volume 3 and online botany databases: IPNI, The plant list and African plants database. As a result, we present for the first time the georeferencing of chromosome number for 276 Asteraceae species and subspecies from 866 localities across Morocco, with their voucher specimen, addresses and authors. We identified the spots of endemism for Asteraceae species with known chromosome numbers in Morocco as Middle Atlas, High Atlas, Anti-Atlas and the Rif. Concerning the ploidy level, our findings indicate that most Asteraceae species in Moroccan flora are diploid, with the chromosome number of 2n = 18 and B-chromosomes occur in arid and semi-arid areas. We also provide species distribution models and presence-only predictions, along with an analysis of how each climatic variable and elevation affect the probability of presence for Asteraceae species. This study significantly contributes to enhancing conservation efforts and assisting researchers in plant cytogenetics.